Graphene based nanocomposites for photocatalytic water treatment and energy applications - Wang, Yinjie (2014)
In recent years, semiconductor photocatalytic process has shown great potential as low-cost, environmental friendly and sustainable treatment technology in the water/wastewater industry. This technology has been widely demonstrated to be capable of removing persistent organic compounds and microorganisms in water. At present, the main barrier that hampers its commercialisation remains on the post-recovery of the catalyst after usage. In this study, it is aimed to develop a new group of composite photocatalysts that utilize ultrathin graphene as the support which facilitates the easy recovery of the catalysts. The introduction of graphene would also enhance the charge separation and transfer during the photocatalytic reactions which could improve the photocatalytic activities. Graphene oxide (GO)-ZnO nanocomposites were synthesized exhibiting high activities for photocatalytic water treatment. Furthermore, the graphene based nanocomposites also have great potential in clean energy applications especially fuel cell application. Reduced GO-Pt nanocomposites were synthesized and evaluated for potential fuel cell application.